The War Game et Who Bombed Birmingham ? : usage politique du mode réflexif - Georges Fournier (Revue LISA)
At a very early stage in the evolution of British television, docudrama was exploited to steer a very large audience towards political and societal issues that needed a national consensus to be addressed. Cathy Come Home remains, in the history of television, the most often cited programme when it comes to assessing the influence of the media on the problems of housing and abortion. More than a mere fictional reprocessing of news, docudrama fitted in nicely with the Reithian ethics of the education of the masses through modern means of communication. Yet, there is more to docudrama than merely informing the population. Its filmmakers, heirs to the famous British tradition of the documentary, imbued their work with a reflexive dimension meant to raise questions on the neutrality of journalism and on the legitimacy of the filmic material in its claim to authenticate reality. Through the analysis of reflexivity to be found in The War Game and Who Bombed Birmingham? this essay will try to show how filmmakers purported to arouse the awareness of television viewers to the subjectivity inherent in the filmic material and in particular in television journalism.